A PRÁTICA DA ASTROLOGIA E A PERSEGUIÇÃO AOS MATHEMATICI NO IV SÉCULO - da Silva, Gilvan Ventura (PHOÎNIX, 2020)
This article intends to discuss the relationship between divination, namely astrology, and the Imperial court during the fourth century A.D. In order to do this, we begin the article by presenting the Roman conceptions about divination and the varied kinds of it from Republic to Empire, including astrology. We then analyse how the public authorities of the Later Roman Empire conceived astrology, and their attempts at forbidding it. Finally, we discuss how astrological knowledge was a very important means of political action in Roman society.